Disturbances of the gut microbiota-derived tryptophan metabolites as key actors in vagotomy-induced mastitis in mice - He, Yuhong; Zhao, Caijun; Su, Niri; Yang, Wencheng; Yang, Hengyi; Yuan, Chongshan; Zhang, Naisheng; Hu, Xiaoyu; Fu, Yunhe (Cell reports (Cambridge), 2024)
Previous studies have demonstrated that gut microbiota dysbiosis promotes the development of mastitis. The interaction of the vagus nerve and gut microbiota endows host homeostasis and regulates disease development, but whether the vagus nerve participates in the pathogenesis of mastitis is unclear. Here, vagotomized mice exhibit disruption of the blood-milk barrier and mammary gland inflammation. Notably, mastitis and barrier damage caused by vagotomy are dependent on the gut microbiota, as evidenced by antibiotic treatment and fecal microbiota transplantation. Vagotomy significantly alters the gut microbial composition and tryptophan metabolism and reduces the 5-hydroxyindole acetic acid (5-HIAA) level. Supplementation with 5-HIAA alleviates vagotomy-induced mastitis, which is associated with the activation of the aryl hydrocarbon receptor (AhR) and subsequent inhibition of the NF-κB pathway. Collectively, our findings indicate the important role of the vagus-mediated gut-mammary axis in the pathogenesis of mastitis and imply a potential strategy for the treatment of mastitis by targeting the vagus-gut microbiota interaction. [Display omitted] •Vagotomy in mice disrupts the blood-milk barrier and induces mastitis•Vagotomy induces disturbances of the gut microbiota-derived tryptophan metabolites•Vagotomy reduces levels of 5-HIAA and inhibits AhR expression in mammary tissue•5-HIAA activates AhR and thereby inhibits the NF-κB pathway to alleviate mastitis He et al. demonstrate that vagotomy induces disturbances of gut microbiota-driven tryptophan metabolism, decreases circulating 5-HIAA levels, disrupts the blood-milk barrier, and induces mastitis in mice. Exogenous supplementation of 5-HIAA activates the AhR and thereby inhibits the NF-κB pathway to alleviate vagotomy-induced mastitis in mice.